Patient-specific dose finding in seamless phase I/II clinical trials. Issue 3 (30th September 2022) - Alam, M. Iftakhar; Shanto, Shantonu Islam
Abstract: This article incorporates a covariate to determine the optimum dose in a seamless phase I/II clinical trial. A binary covariate and its interaction effect are assumed to keep the method simple. Each patient's outcome is assumed to be trinomial, and the continuation ratio model is utilized to model the dose–response data. The Bayesian approach estimates parameters of the dose–response model. Eight plausible dose–response scenarios are investigated to check the proposed methodology. A simulation study shows that covariate consideration can enhance the identification of the optimum dose when it is appropriate to do.